2002
DOI: 10.1002/1099-0682(200206)2002:6<1307::aid-ejic1307>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Monomeric and Platinum-Bonded (1,10-Phenanthroline)thallium Complexes

Abstract: Keywords: MetalϪmetal interactions / Platinum / Thallium / N ligands / NMR spectroscopyOxidative addition of (1,10-phenanthroline)thallium(III) complexes [Tl(phen) n (solv)] 3+ (n = 1−2) (phen = 1,10-phenanthroline) to [Pt(CN) 4 ] 2− in DMSO, in the presence of cyanide ions and in the absence of cyanide ions yielded heterodinuclear metal−metal-bonded complexes, [(NC) 5 Pt−Tl(phen) n (solv)] and [(NC) 4 Pt−Tl(phen) n (solv)] + (n = 0, 1, and 2), respectively. The presence of a direct Pt−Tl bond in the complex i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…There are other unusual donor-acceptor types of adducts, for example thallium (Tl(III)) platinum (Pt(II)); it has been reported that the occupied d z 2 orbital electron pairs can act as potential donor electrons to empty Tl(III) s orbitals to form Pt(II)-Tl(III) metal-metal bond complexes. A large spin-spin coupling constant J( 205 Tl, 195 Pt) was observed from both 205 Tl and 195 Pt NMR spectroscopy, indicating the presence of a strong metal-metal donor-acceptor interaction [5,6].…”
Section: Introductionmentioning
confidence: 96%
“…There are other unusual donor-acceptor types of adducts, for example thallium (Tl(III)) platinum (Pt(II)); it has been reported that the occupied d z 2 orbital electron pairs can act as potential donor electrons to empty Tl(III) s orbitals to form Pt(II)-Tl(III) metal-metal bond complexes. A large spin-spin coupling constant J( 205 Tl, 195 Pt) was observed from both 205 Tl and 195 Pt NMR spectroscopy, indicating the presence of a strong metal-metal donor-acceptor interaction [5,6].…”
Section: Introductionmentioning
confidence: 96%
“…The complexes [(NC) 5 Pt–Tl­(CN) n ] n − , where n = 0, 1, 2, 3, ( 1 – 4 ), and [(NC) 5 Pt–Tl–Pt­(CN) 5 ] 3– ( 5 ), shown in Figure , belong to a fascinating and rare class of organometallic complexes that are stable in aqueous solution and afford direct, nonbridged bonds between Pt and Tl. The bonding in 1 – 4 has been studied theoretically in refs and . Further, it has been shown previously by Kohn–Sham (KS) density functional theory (DFT) calculations that the metal and ligand NMR chemical shifts and, in particular, the J -coupling constants , are strongly impacted by coordination of water at the Tl center.…”
Section: Introductionmentioning
confidence: 99%
“…Strongly bonded coordination compounds are formed by thallium(III) with hard donor atoms such as N and O atoms. Several thallium(III) complexes with N and O donor ligands were reported and characterized by spectroscopy and X-ray diffraction [6][7][8][9][10][11][12][13]. These complexes are of interest owing to their importance for applications in spectroscopy [6][7][8][9], crystallography [10][11][12][13], electronics and optics [ 13,14 ], and nanomaterials [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several thallium(III) complexes with N and O donor ligands were reported and characterized by spectroscopy and X-ray diffraction [6][7][8][9][10][11][12][13]. These complexes are of interest owing to their importance for applications in spectroscopy [6][7][8][9], crystallography [10][11][12][13], electronics and optics [ 13,14 ], and nanomaterials [ 15 ]. 4,7-Diphenyl-1,10-phenanthroline (Ph 2 phen) is a good bidentate ligand, and numerous complexes have been prepared with Ph 2 phen, such as those of gold [ 16 ], indium [ 17 ], mercury [ 18,19 ], rhenium [ 20 ], ruthenium [ 21 ], copper [ 22 ], palladium [ 23 ], platinum [ 24 ], and europium [ 25 ].…”
Section: Introductionmentioning
confidence: 99%